Human Error Examination InAncoiler Device Control Room of Ahvaz Pipe Mill by SHERPA and HET methods at Year 1390 - Somye tajdinan; D Afshari (Salāmat-i kār-i Īrān, 2013)
Background and Aims : industrial development and application of new methods to improve production resulted human errors to be considered more seriously. With this intention, the use of human error identification techniques followed by application of remedy to analysis human errors and decrease of their occurrence probability and criticality became main discussion of scientific and industrial meetings. In addition it can be noticed that by different techniques, human error identification, evaluation and control are performed by better precision and this three-step process is the purpose of this study.     Methods: In this descriptive epidemiological study by using both methods of SHERPA and HET human errors has been detected in the Ancoiler device control room of number 3 factory of Ahwaz Pipe Mill . This study is conducted with the application of two techniques in order to obtain two viewpoints for human error identification. With this intention work sheets of two techniques were completed followed by interview with Ancoiler operator and construction director and factory director.     Results: The most occurred and likely to occur errors in this unit are related to operating errors occurred at different levels of forgetfulness, poor effort, and mistiming the task.     Conclusion: In the control unit the high percentage of errors is allocated to action error. Further the application of two complementary techniques simultaneously can assist to identify errors greatly.